O ensino da avaliação na formação de professores de educação física: um diálogo entre a Ufes/Brasil, Cesmag/Colômbia e Udelar/Uruguai - Frossard, Matheus Lima (2022)
This thesis aims to understand how the educational assessment theme has been prescribed, taught and practiced by teachers who work in the initial teacher education in Physical Education at Ufes/Brazil, Cesmag/Colombia and Udelar/Uruguay. We used the evide